Effect of acid etchant on dentin - Lu, Marina T.; Tiu, Irene T.; Ramos Jr., Aurelio B. (Adviser).
This study was made primarily to determine the effect of acid etchant on dentin permeability. Acid etchants were applied on class V cavity preparation (buccal) of 25 non-carious extracted teeth. The lingual cavities served as the control group of the study. It was found out in the experiment that acid etching procedure increases the permeability of dentin. Thus, it is advisable in clinical practice to prevent etching the dentin and to protect the pulp with a base from whatever irritants coming from the filling material.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.